Electrocatalysis of oxide-based materials for the oxygen reduction and evolution reactions - Mohamed, Rhiyaad (Centre for Catalysis Research, 2016)
Electrochemical devices, such as fuel cells and electrolysers, are said to be at the forefront of a renewable energy technology revolution centred on hydrogen as an energy carrier. These devices rely on the chemical reactions of oxygen, namely the oxidation of water to evolve oxygen (oxygen evolution reaction, OER) and hydrogen , carried out in electrolyser applications or the reverse reaction, the reduction of oxygen to water (oxygen reduction reaction, ORR) producing electricity in the case of fuel cells . Th e reactions of oxygen are however still hindered by extremely slow reaction kinetics. The resultant low efficiencies and associated high cost of electrocatalysts required hinder the widespread commercial success of these devices. In addition, current state - of - the - art electrocatalyst technologies suffer from severe corrosion during operation, presenting an additional barrier to commercialisation and ultimately delaying the successful implementation of a sustainable hydrogen economy. One primary goal of electrocatalysis research is thus the rational design of new materials with higher efficiencies. The fundamental understanding of the behaviour of the electrocatalyst materials towards these reactions will enable greater strides to be achieved in this area. To date much research has been conducted towards this end, however further progress is still required. This thesis details work towards the understanding of a new generation of electrocatalyst technologies for the OER and ORR. This study particularly explore s the use metal oxide based electrocatalyst materials for the oxygen evolution and reduction r eactions as employed in electrolyser and fuel cell applications respectively. The thesis is divided in two parts focusing individually on the OER and ORR respectively. New theoretical and experimental insight into the understanding of oxide electrocataly sts for the OER are discussed in Part I. Part II explores the ORR by studying metal oxides as both catalysts and catalyst support materials in alkaline and acidic environments respectively. Here the emphasis is placed on activity and durability of oxide ma terials under fuel cell operating conditions. The study confirms the promise of oxide based materials and highlights some of the challenges still present in their development for fuel cell applications. The final chapter presents a summary of the thesis. This study provides important insight and contributes towards the further understanding of the use of metal oxides for the OER and ORR. From this study several interesting and promising results were also obtained which warrant further intensive research and investigation. Directions for future research are discussed. [Please note: the full text of this thesis has been deferred until January 2018]